The Triple Play: Social Media Marketing, Brand Trust, and Smartphone Purchase Decisions in Emerging Market - Walean, Ronny H.; Gerungan, Citra Adriana; Mandagi, Deske W. (International Review of Management and Marketing, 2025)
This study aims to investigate the influence of four key dimensions of social media marketing—informative content, entertainment, interactivity, and perceived relevance—on brand trust and their subsequent impact on consumer purchase decisions within the smartphone market. Focusing on emerging markets, this research addresses a critical gap in the literature by exploring these dynamics in the context of Indonesia, a region that has been underrepresented in existing studies. A quantitative research design was employed, utilizing survey-based data collected from 251 smartphone consumers in Indonesia. The data were analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) to assess the hypothesized relationships. The findings reveal that Informativeness is the strongest driver of brand trust, while entertainment, informativeness, and interactivity directly influence purchase decisions. Although brand trust significantly impacts purchase decisions, it does not mediate most social media marketing factors, except for perceived relevance, which affects purchase behavior indirectly through trust. These results offer valuable insights for marketers and practitioners, emphasizing the importance of leveraging engaging and interactive social media strategies to foster brand trust and drive consumer decisions in emerging markets.